Feasibility Study on Providing Bibliotherapy Services in Addiction Treatment Camps Affiliated with State Welfare Organization (SWO) in Tehran Province - Leila Nemati-Anaraki; Nasibeh Shahkhah; Masoud Roudbari; Farzaneh Sardari (Journal of Social Behavior and Community Health, 2023)
Background: The purpose of this study is to evaluate the feasibility of providing bibliotherapy services in addiction treatment camps affiliated with State Welfare Organization (SWO) in Tehran province. The research concerns information resources and manpower, financial resources and technical infrastructure as well as expressing the shortcomings and barriers of this method. Methods: The present study was conducted through a descriptive-survey method with an applied purpose in 2020. A questionnaire was developed by the researcher and validated with the help of experts. In order to assess the reliability of the questions, Cronbach's alpha test was used, which was calculated at 0.925. Sampling was performed using Cochran's formula. The sample size included 66 officials in 66 addiction treatment camps. SPSS software version 22 was used for data analysis Results: The possibility of providing bibliotherapy services in terms of specialized and committed manpower in the field of bibliotherapy in addiction treatment camps was desirable. These centers were not in a good financial position. There was also the possibility of providing bibliotherapy services in terms of the technical infrastructure and manpower. The most effective methods of implementing bibliotherapy in addiction treatment camps were creative and group methods. Lack of budget and trained staff, staff reluctance to provide bibliotherapy services and lack of support from SWO were obstacles which have hindered the provision of bibliotherapy services in addiction treatment camps in Tehran province. Conclusion: The benefits of providing bibliotherapy services in addiction treatment camps include increasing the client's psychological well-being, improving physical condition, preventing the client from returning to drug use, and to some extent, reducing the time of quitting drugs. Assessing and eliminating the shortcomings and barriers of bibliotherapy can play effective roles in the implementation of bibliotherapy.